Value of Albumin–Globulin Ratio as a Predictor of All-Cause Mortality After Non-ST Elevation Myocardial Infarction. (February 2013) - Azab, Basem; Bibawy, John; Harris, Kassem; Khoueiry, Georges; Akerman, Meredith; Selim, Jason; Khalil, Silivia; Bloom, Scott; McGinn, Joseph T.
Low albumin and the albumin–globulin ratio (AGR) were associated with vascular adverse events. Our study explores the AGR as a predictor of mortality after non-ST-segment elevation myocardial infarction (NSTEMI). In an observational study of 570 NSTEMI patients admitted to a tertiary center between 2004 and 2006, patients were stratified into equal tertiles according to AGR. The primary outcome was 4-year all-cause mortality. The 4-year mortality rates in the first, second, and third AGR tertiles were 88 (47%) of 189, 48 (25%)of 190, and 19 (10%) of 191, respectively ( P < .0001). After adjusting for 20 confounding variables, AGR first tertile (AGR <1.12) had a higher mortality versus second tertile (hazard ratio [HR] 2.6, P < .001). Likewise, the AGR second tertile had higher mortality versus the third tertile (AGR ≥1.34; HR 2.3, P = .004). The albumin–globulin ratio is a significant independent predictor of long-term mortality after NSTEMI in patients with normal serum albumin levels. Further studies are needed to explain the underlying mechanisms.